ID 55 – Sensory neuropathy in children presenting with Behr syndrome due to OPA1 mutations. Issue 3 (March 2016) - Boyer, K.; Gitiaux, C.; Nicolas, G.; Magot, A.; Mayer, M.; Barth, M.; Bonneau, D.; Rodriguez, D.; Desguerre, I.; Nguyen The Tich, S.; Péréon, Y.
Abstract : Behr syndrome is a complex genetic disorder occurring in children. It associates optic nerve atrophy and spinocerebellar degeneration (ataxia, pyramidal signs), some patients also presenting with peripheral neuropathy. Transmission is generally autosomal recessive and in some cases is related to mutation in OPA1, a gene encoding a dynamin-related GTPase. 4 children (age 3–14 y-o) with severe visual loss and balance impairment due to OPA1 gene mutations underwent electrodiagnostic (EDX) examination. They presented with early visual loss, mixed cerebellar and proprioceptive ataxia. Some also had pyramidal signs. Compound heterozygous OPA1 mutations were found in all cases. EDX examination demonstrated a severe sensory neuropathy with absent sensory potentials or dramatic decrease of the amplitude, in contrast with normal motor nerve conduction parameters and needle EMG. To date, compound heterozygosity for OPA1 has been proven in only three patients from two unrelated families and neuropathy was not specifically assessed. This is therefore the first report demonstrating the occurrence of severe sensory neuropathy in such cases. Peripheral neuropathy sometimes represents a useful help in the diagnosis of a neurological or metabolic disease occurring in children. The search for sensory neuropathy in children with optic atrophy can be helpful in orientating the genetic diagnosis.